Systemic-pulmonary arteriovenous fistulae with pulmonary hypertension: A case report. Issue 8 (February 2018) - Shi, Yan-Ping; Li, Yi-Dan; Lv, Xiu-Zhang; Yang, Yuan-Hua
Abstract: Background: Arteriovenous (AV) fistulae is an extremely rare disease of vascular malformation that involves fistulae formation between the systemic and pulmonary AV systems. Case representation: This case report describes a rare systemic-pulmonary AV fistulae of congenital origin, accompanied by pulmonary hypertension, as determined by aortic angiography and echocardiography. Conclusion: Characteristics, diagnosis, and therapeutic approaches of this rare abnormality are explored.